University of the Philippines Mindanao E-marketplace (UPMIN E-MARKETPLACE) - Parreño, Eden Jane S. (2010)
With the purpose of bridging the sellers and buyers of the University of the Philippines Mindanao, the University of the Philippines Mindanao E-Marketplace (UPMin E-Marketplace) was created. The UP Min E-Marketplace is an online information system that allows the students, faculty members ans staff to post their products and advertise their services. With this system, residents of the university will be able to broadcast the products/ services thety are offering without having the hassle of looking for an individual who might be interested with the product/ service they are advertising which is also time consuming. Moreover, the university constituents can search and browse for products and services posted by the system's users. This would help the students, faculty members and staff know who offer the product/ services they need. Aside from searching or browsing products and services, the usres can also view the information along with the posted product/ service so that they will know the specification of the product/service. Since products and services are posted in public, there is a system administrator that checks first the products and services added to the system before it would be approved for posting. Aside from products and services, the system administrator can also disable and enable user accounts. As with other information system, the UPMin E-Marketplace can also be further improved by enhancing the encoding structure and GUI, adding more features like a bidding system or shopping cart, and applying web services.